The role of historians in guiding archivists to open up collections and promoting access to archives in South Africa. Issue 1 (1st December 2022) - Schellnack-Kelly, Isabel; Saurombe, Nampombe
Abstract : Research reveals the dwindling number of people consulting archival sources in East and Southern Africa. This is a serious concern, particularly in South Africa, as there is a danger that archives services could follow the same path as the Seattle office of the US National Archives, which closed in January 2020. Many scholars support the notion of opening the archives and their respective collections more expansively and allowing archives to be spaces for the people. Such scholars advocate for open access and transparency by archival institutions indicating that archival practices should be transformed to reflect the history of a nation and the respective communities. All voices should be heard, recorded, remembered and be made accessible to a broad spectrum of users. This paper will unpack several South African narratives that should be opened for public viewing and discussion as well as endeavours to ensure that youth develop an interest and appreciation for archival sources and aspects relating to heritage. This paper is based on a model based on the experience shared by a scholar from India, whose experiences involved a project of re-writing school history textbooks which had been dominated by communal and colonial stereotypes. Several examples have been sourced from different archival institutions in the United States in efforts to bring archives closer to the people and for the inclusion of archival artefacts and resources to be incorporated into teaching and learning activities. It is contended that similar models need to be developed to bring archives closer to the people, allow archives institutions to share their collections and ensure the sustainability of archival institutions and the role historians can play in the achievement of this objective.